Bantuan Sosial Menjadi Ketergantungan: Evaluasi Dampak Program Keluarga Harapan di Kabupaten Pidie Jaya - Taufik, Taufik; Khairunnisa, Khairunnisa; Amirulkamar, Said (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2025)
The Family Hope Program (PKH) is one of the Indonesian government’s primary instruments for poverty alleviation through conditional cash transfers. In Bandar Dua Subdistrict, Pidie Jaya Regency, however, its implementation continues to face challenges, particularly inaccurate beneficiary data and a high level of dependency among recipient households. This study aims to evaluate the implementation of PKH, focusing on data accuracy and its impact on household self-reliance. A qualitative approach was adopted, employing in-depth interviews, field observations, and document reviews related to program execution. Data were analyzed thematically to identify recurring issues and contributing factors. The findings indicate that several beneficiaries no longer meet the eligibility requirements yet remain in the program due to weak data updating and verification mechanisms. Furthermore, a significant proportion of recipients exhibit strong dependence on PKH assistance, which hinders their transition toward economic independence. This dependency is largely influenced by the limited effectiveness of empowerment initiatives and the insufficient use of assistance for income-generating activities. Based on these findings, it is recommended that beneficiary data verification be conducted regularly with the active involvement of village authorities, and that economic empowerment components be reinforced. Strengthening these aspects will help ensure that PKH functions as a transformative intervention aimed at fostering self-reliance, rather than merely serving as a palliative measure for short-term poverty relief.